Crystal structure of Hg(2)SO(4) – a redetermination - Weil, Matthias (International Union of Crystallography, 2014)
The crystal structure of mercury(I) sulfate (or mercurous sulfate), Hg(2)SO(4), was re-determined based on modern CCD data. In comparison with the previous determination from Weissenberg film data [Dorm (1969 ▶). Acta Chem. Scand. 23, 1607–1615], all atoms were refined with anisotropic displacement parameters, leading to higher precision in terms of bond lengths and angles [e.g. Hg—Hg = 2.5031 (7) compared to 2.500 (3)Å]. The structure consists of alternating rows along [001] of Hg(2) (2+) dumbbells (generated by inversion symmetry) and SO(4) (2−) tetrahedra (symmetry 2). The dumbbells are linked via short O—Hg—Hg—O bonds to the sulfate tetrahedra into chains extending parallel to [20-1]. More remote O—Hg—Hg—O bonds connect these chains into a three-dimensional framework.